APPLICATIONS OF CORRELATION AND REGRESSION ANALYSIS TO PRACTICAL PROBLEMS - Karimova Shalola Musayevna; Qirgizboev Umidjon (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article presents ideas and comments on the application of correlation and regression analysis to practical issues.